Development of Jawi Spelling Skills Mobile Applications, 'Oh Jawiku' - Mohd Rashid, Noor Asmina Binti; Md Salleh, Shaharuddin Bin; Md Noor, Norah Binti (International Journal of Interactive Mobile Technologies (iJIM), 2019)
In the past, Jawi script was the main medium of intermediation in Malaya. However, since the emergence of the Roman script, the use of Jawi script has been marginalized causing less awareness among some of the younger generation on the uniqueness of Jawi script. Therefore, a mobile application has been developed to attract students to explore Jawi script especially the spelling of Jawi words. This Jawi Spelling Skills mobile application used constructivism approach and ADDIE model during the development process. This study used quantitative one group pre-test and post-test research design that conducted among 20 students of a primary school. The result shows that the mean value of the post-test was higher than the pre-test which is 89.00 while the percentage of students who liked the Jawi Spelling Skills mobile learning application was high. In conclusion, the application of Jawi Spelling Skills Mobile Learning Application able to attract students to learn Jawi indirectly raised the dignity of Jawi script in the future besides supporting the 21st- century education.